Pathological and Molecular Investigations in the Aborted Fetal Lamb due to the Poxvirus - Beytut, E; Coskun, N; Dag, S; Nuhoglu, H; Karakurt, E; Yilmaz, V; Yildiz, A (Journal of the Hellenic Veterinary Medical Society, 2024)
In this case, the sheeppox virus strain-induced abortion in a ewe and fetal lesions are reported. At the necropsy, pock nodules of varying sizes were seen to scatter over the skin and lungs of the fetus. Histological examination of the pock nodules from the skin and the lungs found typical sheeppox cells and cytoplasmic inclusion bodies. Immunohistochemistry to surfactant proteins (SP) and multi-cytokeratin (MCK) confirmed hyperplasia of type II cells and bronchial lining epithelium in the pock nodes. A polymerase chain reaction (PCR) test using skin nodules confirmed the causing agent is a Capripoxvirus. The phylogenetic comparison of the sheeppox virus (SPPV), goatpox virus (GPPV), and lumpy skin disease virus (LSDV) revealed that the reason for abortion was the sheeppox virus strain.